Implementation of Project-Based Learning Model to Physics Problem Solving Skills of Grade X High School Student - Safitri, Riski; Jumadi, Jumadi; Budiardi, Lia Wahyuningsih; Aifa, Aifa; Putri, Dea Nanda (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to: (1) obtain information on the physics problem-solving skills of class X MIPA 1 SMA students before being taught using a project-based learning model, (2) obtaining information on the physics problem-solving skills of class X MIPA 1 High School students after being taught using a project-based learning model. This type of research is pre-experimental research with a One Group pretest-posttest design consisting of three stages, namely pretest, treatment for 6 meetings, and posttest. In this study there are two variables, namely the dependent variable of problem-solving skills and the independent variable of project-based learning model. The sample in this study was 33 students of class X MIPA 1 SMA, determined by simple random sampling. The results of the study showed that in the pretest, the students' physics learning outcomes obtained an average score of 30 and in the posttest, the average score obtained was 73. The research instrument used was a physics problem-solving skills test that met the valid criteria of 10 items with a normalized N-gain test score of 0.61 so that it can be concluded that the physics problem-solving skills of class X MIPA 1 SMA students increased to the Moderate category.